FANTASY MOVIE IN SPEAKING ACHIEVEMENT OF INDONESIAN EFL LEARNERS - Hanifa, Almira Aisyah; Zaitun, Zaitun (La Ogi : English Language Journal, 2024)
This study shed light on proofing whether or not fantasy movie used as audio-visual media helped the students in improving their speaking achievement. This quantitative pre-experimental research involved 36 students of 8th grade of SMPN 24 South Tangerang as the samples. Both speaking pre- and post-tests were used as the instruments in collecting the data. The data were analyzed quantitatively In four steps; 1) assessing each student’s speaking performance based on the scoring rubric; 2) comparing students’ achievement in the pre-test and in the post-test; 3) presenting the comparison into percentages, and 4) determining the hypothesis. The analysis data showed that most students reached higher achievement in the post-test or after the treatment. In the percentages, 22.2% of the students fell in ‘excellent’ level in the post-test while in the pre-test none of the student was categorized in this criterion. Also, 44.4% of the students who sat in ‘bad’ level in the pre-test, decreased into 11.2% in the post-test. These results indicated that the students made good improvement in their speaking achievement after being taught by using fantasy movie. From those results, this study accepted Ha and rejected H0. To conclude, this research confirmed that fantasy movie used as audio-visual media helped the students in improving their speaking achievement.